(3CMcGe GdOdGdI Ydi JMQjQ GdQSGdIs - (3YHO GdcQje Hf ghGRf Hf YHO Gdedc GHf WdMI GdfjSGHhQj GdbTjQj, CHh GdbGSe, Rjf GdESdGe,J (B465 (3g` s
(3ChdgG (B:s
(3bGd GdTjN GdEeGe CHh jMji RcQjG GdMeO ddg GdPi jSQ SHjd GdSGdcjf Hf ghGRf GdbTjQi s
(3BNQgG (B:s
(3agPg hUjJfG ddeQjOjf fSCd Gddg GdcQje dge GdJhajb hgh Ndb bOQI GdWGYI (B( (3hCf dGjLYdgG (B) (3Ci GdhUjI gPG BNQ eG CQOfG EjQGOg ef TQM QSGdI GdEeGe GdYGQa HGddg JYGdi GdbTjQi s
(3HgG fXGe GdJYbjHIs
(3ebGHdI Ydi fSNI UMjMI bhHdJ eQGQkG Ydi fSN UMjMIs
(3cJH GdeJf HGdNeQI s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs